Grounded Theory : A Short Cut to Highlight a Researchers’ Intellectuality - Omar, Abdul Hafidz; Awang Hamid, Dayang Tiawa; Alias, Norma; Islam, Md. Rajibul (Science Publications, 2010)
Problem statement: Grounded theory is one of the research approaches in qualitative research that enables the researcher to use his/her intellectuality to make sense of and construct a theory based on finding collected throughout the fieldwork. Grounded Theory as suggested in the conventional studies is designated in a very comprehensive manner and involves three level of coding. These coding systems are parallel to Bloom’s Taxonomy where an individual has to first understand the basic knowledge before he/she is able to proceed further. Approach: In the first stage of Grounded Theory, that is, ‘open coding’; data are grouped according to themes or categories. That is where the researcher has to have sufficient knowledge and understanding of the phenomenon being studied. In the second level, that is, ‘axial coding’; the researcher has to connect the themes and make sense of it. At this point, the researcher applies his knowledge and analyses the data. The data is then synthesized and evaluated through ‘selective coding’. Results: These will develop into the draft of the theory that will be tested against other existing theories to form ‘Grounded Theory’. Conclusion: This study shows that the ability to develop a good ‘Grounded theory’ will represent the researchers’ intellectuality.